ANALISIS PENERAPAN METODE PENYUSUTAN ASET TETAP PADA CV MITRA SAHABAT SAMARINDA - Furdawati, Tiya; Robert Hutauruk, Martinus; Mansyur, (OBOR: Oikonomia Borneo, 2019)
The purpose of this study was to determine the implementation of depreciation by CV. Mitra Sahabat Samarinda complies with SFAS 16. From the analysis results for the acquisition price at Cv. Mitra Sahabat and PSAK16 are appropriate or there is no difference. and For the measurement of Cv Mitra Sahabat in accordance with PSAK 16 where the determination of the acquisition cost of fixed assets recorded by Cv. Mitra Sahabat is the accumulation of the entire purchase price plus the costs incurred for the purchase of the fixed assets. For recognition of Cv. Mitra Sahabat is in accordance with PSAK 16, in which the company applies a policy of charging fees in the period in which they are incurred for repairs issued so that the assets remain in good condition. For the reduction of Cv Mitra Sahabat will be adjusted to PSAK 16. And for the presentation of Cv Mitra Sahabat is not in accordance with PSAK 16 because for the presentation of each type of fixed assets such as land, buildings, office inventory and vehicles are not in accordance with PSAK 16 because the fixed assets presented by the company becomes one, namely a Fixed Asset account. Keywords: Fixed Assets, SFAS 16, Depreciation Method.